Analysis of the Implementation of Disaster Management Budget Allocations in Garut Regency West Java Province - Deden Suhendar; Diki Suherman (Khazanah Sosial, 2022)
Several things must be considered in implementing disaster management: fast, precise and priority. However, apart from that, several things hinder the implementation of budget allocations for disaster management activities, so they do not run optimally. This study aims to analyze the implementation of the budget allocation for disaster management in Garut Regency and the factors that hinder and support it by using George C. Edwards III's theory of policy implementation. The method used is descriptive qualitative with data collection techniques using interviews, literature studies on laws and regulations and other related documents. The analysis technique used is data reduction, data presentation and conclusion drawing. The results showed that implementing the disaster management budget allocation in Garut Regency had been carried out by the applicable laws and regulations. This is supported by communication factors and good attitude of implementers, complete Standard Operating Procedures, smooth coordination with other agencies and several resources that have been met. Unfulfilled resources are staff shortages in terms of quantity but this can be overcome with good cooperation in overcoming them. In addition, there are several external factors that affect the implementation of the budget in Garut Regency which are beyond the control of the government, for this reason, government innovation is needed to overcome this.